Displacement and Dilaceration of Permanent Teeth as a sequel of trauma to Primary Teeth diagnosed by CBCT: A Rare Case Report - Pokharel, Pooja; Nimbeni, Shruti B; Nimbeni, Basavaraj S; Rout, Sourav K (Orthodontic Journal of Nepal, 2016)
Dentoalveolar trauma to the primary teeth can result in displacement, dilaceration, discoloration, delayed eruption and impaction of permanent teeth. Displacement and dilaceration of permanent teeth is the most common sequel of such injuries. The severity of such condition depends on the force of impact, region of trauma and stage of tooth development of the permanent tooth. In the present case, there was dentoalveolar trauma to primary teeth as a result of which there was displacement of the permanent incisors into the nasal floor and 90 degree dilaceration at the cementoenamel junction. The treatment included surgical removal of the displaced teeth, exposure of palatally impacted canines followed by orthodontic correction and prosthodontic replacement of the extracted teeth. Cases of dentoalveolar trauma should be critically evaluated and advanced diagnostic aids like CBCT must be used for a clear picture of the case and better treatment planning. Treatment of such cases should be followed up for a longer period of time